Vote buying II: legislatures and lobbying - Eddie Dekel; Matthew O. Jackson; Asher Wolinsky (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2006)
We examine the consequences of lobbying and vote buying, assuming this practice were allowed and free of stigma. Two .lobbyists. compete for the votes of legislators by oþering up-front payments to the legislators in exchange for their votes. We analyze how the lobbyists.budget constraints and legislator preferences determine the winner and the payments.
Keywords: P16; C72; 330; vote buying; lobbying; legislatures; political economy; Ökonomische Theorie der Demokratie; Politische Partei; Spieltheorie; Wahl; Wahlverhalten; Theorie